Dissolved Zn and its speciation in the northeastern Indian Ocean and the Andaman Sea - Kim, Taejin; Obata, Hajime; Gamo, Toshitaka (Frontiers in Marine Science, 2015)
Total dissolved Zn and Zn speciation were investigated by cathodic stripping voltammetry (CSV) in the northeastern Indian Ocean and the Andaman Sea. Vertical distributions of total dissolved Zn concentration (CZn) in the northeastern Indian Ocean and the Andaman Sea reflect that the deep water from the Andaman Sea was rapidly replaced by incoming waters from the northeastern Indian Ocean across the sills and was homogenized by vertical mixing. In the Andaman Sea, CZn at the near surface, < 50 m in depth, ranged from 0.33 nM to 1.14 nM at the southernmost station, which is an order of magnitude higher than those at the northernmost station, 0.03–0.22 nM, where is in close proximity to the estuaries of the Irrawaddy and Salween rivers. However, the Si concentration in the near surface water, 16.3 μM, was highest at the northernmost station of the Andaman Sea. In the northeastern Indian Ocean, only one sample was applied to estimate total ligand concentrations (CL) and conditional stability constants (〖K^'〗_(ZnL,Zn^(2+) )) for organic complexation of Zn. The CL and 〖K^'〗_(ZnL,Zn^(2+) ) in the northeastern Indian Ocean were 0.5 nM and 10.0, whereas those of the Andaman Sea were 0.4 nM–0.9 nM and 9.6–11.4, respectively. We observed no clear relationship between chlorophyll a (Chl a) and CL in the Andaman Sea. Various sources of Zn complexing ligands might be derived in the Andaman Sea, not only from bacteria and phytoplankton, but also from the Irrawaddy–Salween rivers.